Nationwide improvement of rectal cancer treatment outcomes in Norway, 1993–2010. (26th November 2015) - Guren, Marianne G.; Kørner, Hartwig; Pfeffer, Frank; Myklebust, Tor Å.; Eriksen, Morten T.; Edna, Tom-Harald; Larsen, Stein G.; Knudsen, Kristin O.; Nesbakken, Arild; Wasmuth, Hans H.; Vonen, Barthold; Hofsli, Eva; et al.
Abstract : Background. The Norwegian Rectal Cancer Project was initated in 1993 with the aims of improving surgery, decreasing local recurrence rates, improving survival, and establishing a national rectal cancer registry. Here we present results from the Norwegian Colorectal Cancer Registry (NCCR) from 1993 to 2010. Material and methods. A total of 15 193 patients were diagnosed with rectal cancer in Norway 1993–2010, and were registered with clinical data regarding diagnosis, treatment, locoregional recurrences and distant metastases. Of these, 10 796 with non-metastatic disease underwent tumour resection. The results were stratified into five time periods, and the treatment outcomes were compared. Recurrence rates are presented for the 9785 patients who underwent curative major resection (R0/R1). Results. Among all 15 193 patients, relative five-year survival increased from 54.1% in 1993–1997 to 63.4% in 2007–2010 (p < 0.001). Among the 10 796 patients with stage I–III disease who underwent tumour resection, from 1993–1997 to 2007–2010, relative five-year survival improved from 71.2% to 80.6% (p < 0.001). An increasing proportion of these patients underwent surgery at large-volume hospitals; and 30- and 100-day mortality rates, respectively, decreased from 3.0% to 1.4% (p < 0.001) and from 5.1% to 3.0% (p < 0.011). Use of preoperative chemoradiotherapy increased from 6.5% in 1993 to 39.0% in 2010 (p < 0.001). Estimated local recurrence rate after major resection (R0/R1) decreased from 14.5% in 1993–1997 to 5.0% in 2007–2009 (p < 0.001), and distant recurrence rate decreased from 26.0% to 20.2% (p < 0.001). Conclusion. Long-term outcomes from a national population-based rectal cancer registry are presented. Improvements in rectal cancer treatment have led to decreased recurrence rates of 5% and increased survival on a national level.